Evaluation of two brazilian native yeast strains (Pichia kudriavzevii) in craft beer (Research, Society and Development, 2022)
Beer production is an ancient biotechnological process and since yeast as discovered to be responsible for the transformation of barley wort into beer, studies have been carried out with the aim of understanding the behavior of these microorganisms. This work aimed to study the application of two strains of yeasts of the species Pichia kudriavzevii, isolated in the Brazilian Midwest for the production of craft beer and to analyze the occurrence of bioaromatization, with the production of volatile organic compounds (VOC) and to evaluate the sensory perception of the results with untrained end consumers through a quick sensory methodology called Check All That Apply (CATA). For this purpose, three batches of beer were produced and inoculated with commercial yeast (Saccharomyces cerevisiae, the control) and two strains of the same species, called Pichia kudriavzevii BB1 and Pichia kudriavzevii BB2. A total of 28 volatile organic compounds that differentiated the control of the Pichia BB1/BB2 group were detected, being 20 esters, 2 alcohols, 5 carboxylic acids and 1 hydrocarbon. There was no difference among the Pichia kudriavzevii BB1 and BB2 samples (p>0.05) in the sensory analysis using the CATA methodology. It was possible to distinguish two clusters between the tasters according to the habit of consuming craft beer, and those who consumed frequently, assigned a higher score in the hedonic test. It was concluded that Pichia kudriavzevii BB1 and BB2 influenced the beer bioaromatization, improving the acceptance test score with the tasters.